Abnormal Returns of Bank Stocks and Their Factor-Analyzed Determinants - F. F. Cheng; M. Ariff (Journal of Accounting, Business and Management (JABM), 2007)
There is strong evidence that the earnings response coefficients are highly significant in several investigations over 40-years on the relation between abnormal returns of stocks and accounting earnings. Attempts to include non-earnings accounting variables in such research have led to mixed results. This paper takes a new approach using factor analysis to identify potential bank-relevant factors to examine if these factors in addition to earnings are also correlated with abnormal returns of bank shares. Factor analysis is used to reduce 21 accounting and financial ratios into four factors, which were then input in the regressions. The results show high R-square in the regression between abnormal returns and (a) earnings change factor, which indicates a better fit than in studies of non-banks on the earning-to-price relation. Further evidence found is that (b) credit risk factor has significant information content beyond earnings change in the regression with abnormal returns of bank shares. The other two factors are not found to be significant.